Efficient continuous catalytic process for production of bisphenol A - Dhotre, Kapil; Patil, Chetana Rupak; Tarade, Komal P.; Markandeya, Nishant; Pathak, Abhishek; Bhongale, Sunil S.; Kamble, Sanjay P. (Organic Process Research & Development, 2025)
Bisphenol A (BPA) is a versatile chemical compound that is essential for producing durable polycarbonate plastics and strong epoxy resins, which are integral to numerous everyday products. In the present study, BPA was prepared using phenol and acetone using a highly active and reusable ion-exchange resin (IER) Lewatit K1131S as the catalyst. Under optimized conditions, an acetone conversion of 84% and a BPA selectivity of 94% were achieved. The produced BPA was further purified, resulting in a 96% isolated yield with 99.5% purity. The reusability of Lewatit K1131S has been studied, and it was found that it can be reused multiple times without affecting the selectivity for BPA. The kinetics of the reaction was studied using the Langmuir-Hinshelwood model; it was found that the reaction follows pseudo-first-order kinetics, and the apparent activation energy was determined to be 12.7 kJ/mol. A continuous pilot scale process for the production of BPA using a fixed-bed reactor (packed with ion-exchange resin) has been developed. Pilot plant trials were conducted at different flow rates such as 200, 300, and 500 g/h, and a downstream processing methodology using an agitated thin film evaporator (ATFE) was employed for the BPA purification. This resulted in high throughput, producing 99.2% isolated BPA yield with 99.5% HPLC purity. Additionally, the robustness and viability of the catalyst were assessed at a flow rate of 200 g/h, producing 22.5 kg of BPA per kg of catalyst, highlighting its cost-effectiveness, stability, and resistance to deactivation, which shows its suitability for industrial-scale applications. The environmental viability of the process was further evaluated by using the E-factor and Process Mass Intensity (PMI) metrics. The estimated E-factor was 0.3118, while the corresponding PMI was 1.3935. These lower values indicate reduced waste generation, improved material efficiency, and enhanced sustainability of the process.
Keywords: bisphenolA; BPA purification; Continuous process; E-factor; ion-exchange resins (IER); PMI; process optimization; reactionkinetics

Condensation of bioderived guaiacol with acetaldehyde for the synthesis of bisguaiacol-E: a biobased alternative to bisphenol-A - Dhotre, Kapil; Tarade, Komal P.; Kamble, Sanjay P. (Industrial & Engineering Chemistry Research, 2026)
Bisguaiacol-E (BGE) has emerged as a biobased and sustainable alternative to bisphenol-A (BPA) for the production of materials intended for direct contact with humans and animals, including baby feeding bottles and food packaging. In the present study, BGE was synthesized from bioderived guaiacol and acetaldehyde via acid-catalyzed condensation using a highly efficient and reusable ion-exchange resin, Purolite C124SH. Under optimized conditions, the process achieved 96% guaiacol conversion with 100% selectivity toward BGE. The crude product was purified to obtain BGE in 95% isolated yield and 100% purity. The reusability of Purolite C124SH was evaluated over multiple reaction cycles. After five consecutive reuse cycles, guaiacol conversion and BGE selectivity declined by approximately 25-26% and 20-22%, respectively. However, after regeneration by methanol treatment, the catalyst recovered its activity and maintained a consistent performance over the subsequent three cycles. These results demonstrate the catalyst's regenerability, robustness, and resistance to deactivation, highlighting its potential for cost-effective industrial application. The kinetic study indicates that the condensation of acetaldehyde with guaiacol to form BGE over the Purolite C124SH resin catalyst can be described by a pseudohomogeneous kinetic model. The reaction follows apparent pseudo-first-order behavior, with an activation energy of 43.5 kJ mol-1, suggesting a minimal contribution from external mass-transfer limitations under the investigated conditions. Moreover, at the optimized reaction conditions, the estimated space-time yield (STY) was 0.42 kg L-1 h-1, corresponding to an apparent reaction rate constant of 0.5 h-1. Furthermore, the physicochemical properties of the synthesized BGE were compared with those of reported BGF (Bisguaiacol-F) and BPA, showing strong alignment and confirming its applicability as a safer substitute. The environmental performance of the process was assessed using green chemistry metrics. The calculated E-factor (0.2) and Process Mass Intensity (PMI - 1.27) indicate low waste generation, high material efficiency, and improved sustainability. Overall, the developed methodology offers a clean, efficient, and scalable route for producing BGE as a viable biobased replacement for BPA.